Epidemiological profile and spatio-temporal pattern of infant deaths in a district of North India during 2016-2019 - Aman Sachdeva; Ramesh Verma; Ginni Agrawal; Vinay; Jitesh Satija (Wolters Kluwer Medknow Publications, 2023)
Background: Infant mortality is an important health indicator of a population given its strong link to socioeconomic status, health service access, and quality and maternal health. The declining trend of Infant Mortality Rate has been observed in India where it reduced from 89 deaths per 1000 live births in 1990 to 28 deaths per 1000d live births in 2019. Most of the studies regarding the trend of infant mortality are state-based, however, state-level infant mortality has masked the intradistrict clustering of individual infant deaths. Hence, this study was planned with an objective to study the trend of infant mortality at the district level. Material and Methods: A retrospective study was conducted in the district Rohtak of Haryana using the data collected regarding infant deaths. The collected data regarding addresses were geocoded. The resulting layer was then analyzed using QGIS v3.10. The descriptive data was analyzed using SPSS v20.0. Result: In total, 1336 infant deaths during the study period were included. A declining trend of infant mortality was observed over the study period. The number of grids (25 km2) reduced from 18 in 2016 to 10 in 2019 depicting a reduction in the areas with more than expected count. Conclusion: This study emphasizes on the importance of using the geographic information science technique in identifying local hotspots within the district so as to find areas that need more support and observation.